The Implementation of Project-Based Learning Model towards the Ability to Understanding Mathematical Concepts - Junia, Junia; Fitrianti, Yuli; Septy, Liana (Jurnal Pendidikan Matematika, 2023)
The ability to understand mathematical concepts is an important part of learning objectives. The provided material is not only to be memorized, but also students need to understand the entire concepts of the material being studied. This research aims to determine the effect of implementing the PjBL model on the ability to understand mathematical concepts and how much students' interest in learning as a response to the application of the PjBL learning model in classVIIby using algebra material atSMPNegeri 36 OKU in the academic year 2022/2023. The research used a quantitative research method with a One Group Pretest-Posttest design. The research population was all members of classVIIstudents. The sample used was only 1 class with a saturated sampling technique where all members of the population were used as samples. The techniques in collecting the data were tests, questionnaires, and observations. The data test analysis technique used the Z-Test, the questionnaire was measured using a Likert scale, and observations were measured using the Guttman scale. From the research results, the z table value = -1.95996398454005 and the calculated z = -5.8488123797208 with a sig of 0.00 < 0.05 where the calculated z < -z table concludes that learning with the PjBL model has an effect on the ability to understand mathematical concepts and The response to students' interest in learning shows that the majority are in a good category. However, it is necessary to adapt to this learning process because this learning model is being used for the first time and several meetings are needed to complete the project. Kemampuan pemahaman konsep matematis salah satu bagian penting dalam tujuan pembelajaran. Materi yang diberikan bukan semata-mata untuk dihapalkan, tetapi peserta didik harus mengerti agar dapat memahami konsep materi yang dipelajari. Permasalahan yang dihadapi oleh peserta didik karena mengalami kesulitan dalam membedakan unsur-unsur bentuk aljabar, kesulitan mensubstitusikan persamaan, dan  kesulitan dalam operasi hitung bentuk aljabar. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan model pembelajaran PjBL terhadap kemampuan pemahaman konsep matematis dan berapa besar respon minat belajar peserta didik terhadap penerapan model pembelajaran PjBL pada materi bentuk aljabar kelas VII SMP Negeri 36 OKU Tahun 2022/2023. Metode penelitian yang digunakan adalah metode kuantitatif dengan desain One Group Pretest-Posttest. Populasi penelitian adalah peserta didik kelas VII. Sampel yang digunakan hanya 1 kelas dengan tehnik sampling jenuh yang mana semua anggota populasi digunakan sebagai sampel. Tehnik pengumpulan data yang digunakan adalah tes, angket, dan observasi. Tehnik analisis data tes menggunakan Uji-Z, angket diukur dengan skala Likert, dan observasi diukur dengan skala Guttman. Dari hasil penelitian nilai –z tabel = -1,95996398454005 dan z hitung = -5,8488123797208 dengan sig 0,00 < 0,05 yang mana z hitung < -z tabel disimpulkan bahwa pembelajaran dengan model PjBL berpengaruh terhadap kemampuan pemahaman konsep matematis dan respon minat belajar peserta didik menunjukkan bahwa sebagian besar pada kategori baik. Walaupun, perlu adaptasi dengan proses pembelajaran ini karena model pembelajaran ini baru pertama kali digunakan dan dibutuhkan beberapa pertemuan untuk menyelesaikan proyek.